Delivering an Online Global Masters Degree: How Can We Manage Learning in a Managed Learning Environment? - Quinsee, Susannah; Wood, Jo (Proceedings of the International Conference on Networked Learning, 2002)
This paper considers ways in which online education can be managed and monitored to ensure that independent learning is promoted and students gain access to high quality resources. Using a distance learning Masters course as a case study, we evaluate the effectiveness of three aspects of the online learning experience.